Dynamics of civil structures. Volume 2 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics, 2017 - Pakzad, Shamim; Caicedo, J. M. (Conference proceedings of the Society for Experimental Mechanics series., 2017)
Dynamics of Civil Structures, Volume 2: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the second volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of the Dynamics of Civil Structures, including papers on: · Modal Parameter Identification · Dynamic Testing of Civil Structures · Control of Human Induced Vibrations of Civil Structures · Model Updating · Damage Identification in Civil Infrastructure · Bridge Dynamics · Experimental Techniques for Civil Structures · Hybrid Simulation of Civil Structures · Vibration Control of Civil Structures · System Identification of Civil Structures.